Open posteromedial dislocation of ankle without associated fractures - Yadlapalli, Saipramod; Paparao, Bezawada; Kotha, Guruvardhan Kumar Venkata; Elaprolu, Praveen (International Journal of Research in Orthopaedics, 2021)
Dislocation of ankle without associated malleoli or talar fractures is a rare presentation. There is no established standard treatment for this condition. Most of them are treated by immediate reduction followed by immobilisation for 6-9 weeks. Majority of them recover without any complications. Here we reported a case of 33 year old man who was injured due to fall from a height, His ankle was deformed with a laceration over lateral side of ankle. Plain radiograph revealed posteromedial tibiotalar dislocation without any associated fractures. Immediate reduction and suturing was performed. At 5 months postoperative review patient was able to perform his daily routine without any instability or complaints.